The Fekete-Szegö coefficient functional of quasi-subordination Concept - Saray, Noor Fouad; Juma, Abdul Rahman S. (Iraqi Journal of Science, 2025)
In this article, we explore a specific subclass of the collection of analytic functions in a unit disk . This subclass is determined by quasi-subordination, and we provide exact limits for the Fekete-Szegö functional (that is, for functions in this class. The study produces well-defined borders, and we also talk about different results for new classes while making links to the ones that already exist.